History of river channel modifications - A review - M. A. Mohammed-Aslam,; A. Balasubramanian, (African Journal of Environmental Economics and Management, 2023)
Many river basins have witnessed episodes of modifications and shifts in its courses in the geological past. The study of these aspects can be regarded as part of a trend towards the understanding and explanation rather than depiction of how rivers adjust, under varied terrains of landform behaviour. The methodological appraisals that arise from such intensive research are illustrated in this paper using a detailed investigation of river reach with a special emphasis on palaeochannels and channel modification. The proper evaluation of the past works on channel modifications is expected to provide more insight into not only the theoretical concepts of channel metamorphosis but also to the realistic development of natural resources. For successful planning and management of the water resources, it is essential to evaluate the actual surface and subsurface signatures of the dynamic river systems.